Diffraction imaging using azimuthal plane-wave destruction - Merzlikin, D.; Fomel, S.; Bona, Andrej (2016)
© 2016 SEG.Diffraction imaging is a useful tool for seismic reservoir characterization because it can provide additional information about small-scale heterogeneities. Diffractions and reflections coexist on seismic data. Because the latter often mask diffractions, a separation procedure is required. Plane-wave destruction workflow has been proven to be an effective and robust technique for diffraction and reflection separation. In 3D, it can be performed in either the inline or crossline direction. We combine inline and crossline plane-wave destructions to account for variable azimuth of diffraction edges. The proposed approach allows for estimating edge diffraction orientation, which is valuable additional information to aid the interpreter.